Alloy powder suitable for surface treatment of petroleum screw and application method of alloy powder

By using specific alloy powder on the surface of the petroleum screw for thermal spraying and laser cladding, the problem of poor interface bonding performance is solved, and the high temperature, corrosion and wear resistance after the screw surface treatment is significantly improved.

CN119710526AActive Publication Date: 2025-03-28SHANGHAI ZHUYU MATERIAL TECH CO
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510220730.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-27
Publication Date
2025-03-28
Estimated Expiration
2045-02-27

AI Technical Summary

Technical Problem

In the prior art, when laser cladding is used for laser cladding, the interface bonding performance is poor, resulting in unsatisfactory screw surface treatment effect and it is difficult to achieve the expected enhancement effect.

Method used

An alloy powder is used, including the first powder raw material (tungsten, cobalt, carbon, aluminum oxide), the second powder raw material (chromium, boron, silicon, nickel) and the functional auxiliary mixture raw material (molybdenum, titanium, niobium), and the reinforcement layer with high hardness, good toughness and wear resistance are formed by thermal spraying and laser cladding.

Benefits of technology

The interface bonding performance between different alloy powders is significantly improved, and the high temperature, corrosion and wear resistance after screw surface treatment is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of metal powder processing, and particularly discloses alloy powder suitable for surface treatment of a petroleum screw and an application method of the alloy powder. The invention discloses alloy powder suitable for surface treatment of a petroleum screw. The alloy powder comprises a first powder raw material, a second powder raw material and a functional auxiliary mixing agent raw material, the first powder raw material comprises the following components in parts by weight: 65-75 parts of tungsten; 20 to 25 parts of cobalt; 4-8 parts of carbon; 3-5 parts of aluminum oxide; the second powder raw material comprises the following components in parts by weight: 9-12 parts of chromium; 5-8 parts of boron; 4-6 parts of silicon; 50 to 80 parts of nickel; the functional auxiliary mixing agent raw material comprises the following components in parts by weight: 8-10 parts of molybdenum; 80 to 90 parts of titanium; 3-5 parts of niobium; the weight part ratio of the first powder raw material to the second powder raw material to the functional auxiliary mixture raw material is (0.8-1.2): 1: (0.2-0.4). According to the preparation method, the interface bonding performance among different powder raw materials can be improved, and the high-temperature-resistant, corrosion-resistant and wear-resistant alloy powder suitable for the petroleum screw rod is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of metal powder processing, and more specifically, to an alloy powder suitable for surface treatment of a petroleum screw and an application method thereof. Background Art

[0002] The petroleum screw pump is a widely used device in oil production. It is particularly suitable for conveying high-viscosity, sand-containing, and gas-containing crude oil. The working principle is to transmit power from the power source to the drive head, and then to the light rod through the reduction device, and finally to the screw pump at the bottom of the well. The rotor and stator of the screw pump form a sealed cavity. As the rotor rotates, the sealed cavity moves continuously, thereby realizing the suction and discharge of crude oil.

[0003] The screw rotors used in petroleum screw pumps face harsh working conditions with high temperature, strong corrosion, high wear and other characteristics during operation. General alloy steel cannot meet the requirements of use at all. At present, most of the rotors produced at home and abroad are plated with hard chrome layer on the surface, but this kind of rotor has poor corrosion resistance when used in salt water slurry. In severe cases, the entire motor assembly will be scrapped, which directly affects the service life of the screw. The use of stainless steel rotors is more expensive, generally 4-5 times that of hard chrome plating, which directly limits the scope of use. Therefore, spraying a certain heat-resistant, corrosion-resistant and wear-resistant alloy on the surface of the screw rotor is a very suitable surface treatment method.

[0004] For example, the invention patent application with patent publication number CN115383110A discloses a spherical tungsten carbide and nickel-based alloy mixed powder for screw reinforcement and a laser cladding method, wherein the mixed powder is formed by mixing spherical tungsten carbide powder and nickel-based alloy powder. Based on the total mass of the mixed powder, the mass percentage of the spherical tungsten carbide powder is 60-85%, and the remainder is nickel-based alloy powder. The present invention mixes spherical tungsten carbide powder and nickel-based alloy powder and then clads them on the working surface of the part. By controlling the specific gravity of the spherical tungsten carbide and nickel-based alloy powder, the performance of the spherical tungsten carbide is maximized. The two powders are mixed to form a high hardness, good toughness and wear-resistant reinforcement layer on the surface of the workpiece with a complex curved surface.

[0005] Regarding the above-mentioned related technologies, the inventors believe that when using two or more mixed powders for laser cladding on the screw surface, although it can bring about the corresponding superposition enhancement effect, the interface bonding performance between different powders is not good, which makes it difficult to achieve the expected enhancement effect. The effect brought by the overall application still needs to be improved.

[0006] Therefore, it is urgent to propose a solution to solve the above technical problems. Summary of the invention

[0007] In order to improve the interface bonding performance between different powder raw materials and obtain high temperature resistant, corrosion resistant and wear resistant alloy powder suitable for petroleum screws, the present application provides an alloy powder suitable for surface treatment of petroleum screws and an application method thereof.

[0008] In the first aspect, the present application provides an alloy powder suitable for surface treatment of petroleum screws, using the following technical solution: An alloy powder suitable for surface treatment of a petroleum screw, comprising a first powder raw material, a second powder raw material and a functional auxiliary mixing agent raw material; The first powder raw material comprises the following components in parts by weight: Tungsten 65-75 parts; Cobalt 20-25 parts; Carbon 4-8 parts; 3-5 parts of aluminum oxide; The second powder raw material comprises the following components in parts by weight: Chromium 9-12 parts; Boron 5-8 parts; Silicon 4-6 parts; Nickel 50-80 parts; The functional auxiliary mixture raw material comprises the following components in parts by weight: Molybdenum 8-10 parts; Titanium 80-90 parts; Niobium 3-5 parts; The weight ratio of the first powder raw material, the second powder raw material and the functional auxiliary mixture raw material is (0.8-1.2):1:(0.2-0.4).

[0009] By adopting the above technical scheme, in the first powder raw material, tungsten can improve hardness, wear resistance, high temperature resistance and chemical stability; cobalt can promote the formation of crystal nuclei of liquid alloy in the alloy, thereby improving the processing performance, corrosion resistance, strength, etc. of the alloy; carbon can promote the grain boundary movement of the alloy, improve the intercrystalline strength and plasticity, thereby enhancing the hardness and wear resistance of the alloy; alumina can effectively resist mechanical wear and exert good corrosion resistance. In the second powder raw material, chromium can improve strength and hardness, wear resistance, corrosion resistance and thermal strength; boron can enhance hardness and wear resistance; silicon can enhance mechanical properties, corrosion resistance, heat resistance, castability and machinability; nickel can enhance the strength, corrosion resistance, high temperature stability and oxidation resistance of the alloy. By mixing the first powder raw material and the second powder raw material, better heat resistance, corrosion resistance and wear resistance can be exerted after the surface treatment of the screw rotor. At the same time, functional auxiliary admixture raw materials are also used in the alloy powder, among which molybdenum can form a solid solution with other elements, and can strengthen and harden the grain boundaries of the alloy, and reduce the dislocation movement of the grain boundaries; titanium can refine the grains, eliminate and absorb the impurity elements in the alloy; niobium can enhance the activity of the melt, thereby increasing the degree of interface reaction; through the compounding of the three, the functional auxiliary admixture raw materials can significantly improve the interface bonding performance between different alloy powders when mixed with the first powder raw material and the second powder raw material, so that the cooperation between the first powder raw material and the second powder raw material can play a corresponding effect far close to the expected effect, and finally obtain a high temperature resistant, corrosion resistant and wear resistant alloy powder suitable for petroleum screws.

[0010] Preferably, the weight ratio of the first powder raw material, the second powder raw material and the functional auxiliary mixture raw material is 1:1:0.3.

[0011] By adopting the above technical scheme, the first powder raw material, the second powder raw material and the functional auxiliary mixture raw material in the above weight ratio can have a relatively excellent coordination effect when mixed and applied, so that the functional auxiliary mixture raw material can fully act on the common compounding enhancement of the first powder raw material and the second powder raw material, and bring about a better interface bonding improvement effect, thereby obtaining an alloy powder with excellent high temperature resistance, corrosion resistance and wear resistance suitable for the surface treatment of petroleum screws.

[0012] Preferably, the first powder raw material comprises the following ingredients in parts by weight: Tungsten 70 parts; Cobalt 22 parts; 4 parts of carbon; 4 parts of aluminum oxide.

[0013] By adopting the above technical scheme, the first powder raw material composed of the above-mentioned component ratio enables each component to fully play its role in the alloy system of the first powder raw material, and the coordination between each other is better, thereby making the high temperature resistance, corrosion resistance and wear resistance brought about by the application of the first powder raw material better.

[0014] Preferably, the second powder raw material comprises the following ingredients in parts by weight: Chromium 10 parts; Boron 6 parts; Silicon 5 parts; Nickel 65 parts.

[0015] By adopting the above technical scheme, the second powder raw material composed of the above-mentioned component ratio enables each component to fully play its role in the alloy system of the second powder raw material, and the coordination between each other is better, thereby making the high temperature resistance, corrosion resistance and wear resistance brought about by the application of the second powder raw material better.

[0016] Preferably, the functional auxiliary mixture raw material comprises the following components in parts by weight: Molybdenum 10 parts; Titanium 85 parts; Niobium 5 parts.

[0017] By adopting the above technical scheme, when the molybdenum, titanium and niobium components are used in combination, the composite effect between them is relatively excellent, and can bring about a better improvement and enhancement effect on the interface bonding between the first powder raw material and the second powder raw material, so that the final alloy powder suitable for the surface treatment of petroleum screws can exert relatively excellent high temperature resistance, corrosion resistance and wear resistance after application.

[0018] Preferably, the alloy powder suitable for surface treatment of petroleum screw has a particle size of 13-18 μm.

[0019] By adopting the above technical solution, the alloy powder of the above particle size is convenient for treating the surface of the petroleum screw when used, and under this particle size specification, the first powder raw material, the second powder raw material and the functional auxiliary mixture raw material can also be mixed more fully, and when used, the effect of cooperation between them is better, and the high temperature resistance, corrosion resistance and wear resistance brought by them are more outstanding.

[0020] In a second aspect, the present application provides an application method of alloy powder suitable for surface treatment of petroleum screws, which adopts the following technical solution: An application method of alloy powder suitable for surface treatment of petroleum screws comprises the following steps: (1) Preparing a first powder raw material, a second powder raw material and a functional auxiliary mixture raw material; (2) After the first powder raw material, the second powder raw material and the functional auxiliary mixture raw material are mixed, the surface of the screw rotor is thermally sprayed, and a cladding layer is obtained by laser cladding to complete the surface treatment of the screw rotor.

[0021] By adopting the above technical scheme, the first powder raw material, the second powder raw material and the functional auxiliary mixture raw material can be applied by simply mixing them, and the overall operation is relatively convenient; then in the application process, thermal spraying is performed first, and then laser cladding is performed, which can form a relatively sufficient, complete and stable interface bonding between the first powder raw material, the second powder raw material and the functional auxiliary mixture raw material, and the obtained cladding layer has better quality, can bring excellent high temperature resistance, corrosion resistance and wear resistance, and thus the surface treatment effect of the screw rotor is relatively excellent.

[0022] Preferably, the thickness of the cladding layer in step (2) is 20-40 μm.

[0023] By adopting the above technical solution, the cladding layer of the above thickness can meet the requirements of surface treatment of the screw rotor, and can exert excellent and stable high temperature resistance, corrosion resistance and wear resistance during the application process.

[0024] Preferably, in step (2), the temperature of thermal spraying is 1000-1400°C.

[0025] By adopting the above technical solution, when the mixture of the first powder raw material, the second powder raw material and the functional auxiliary mixture raw material is subjected to thermal spraying treatment, the selection of the above temperature enables the mixture to be more evenly and stably attached to the surface of the screw rotor, and the first powder raw material, the second powder raw material and the functional auxiliary mixture raw material can also form a pre-bonding with each other, which is more conducive to the formation of a stable and excellent interface bonding after subsequent laser cladding.

[0026] Preferably, in step (2), the laser wavelength of the laser cladding is 10-12 μm, the laser scanning speed is 0.6 m / min-1.2 m / min, and the laser power density is 10-20 kW / cm 2 .

[0027] By adopting the above technical solution, during the laser cladding process, the selection of the above process parameters can enable the first powder raw material, the second powder raw material and the functional auxiliary mixture raw material to be fully coordinated and combined, which is conducive to obtaining a cladding layer with better application quality, thereby bringing better surface treatment effect to the screw rotor.

[0028] In summary, this application has the following beneficial effects: The present application uses a functional auxiliary mixed agent raw material containing molybdenum, titanium and niobium, which can bring excellent interface bonding improvement effect to different alloy powders, significantly enhance the bonding between the first powder raw material and the second powder raw material, and cooperate with the first powder raw material and the second powder raw material to exert a corresponding effect far close to the expected effect, thereby finally obtaining a high temperature resistant, corrosion resistant and wear resistant alloy powder suitable for petroleum screws. DETAILED DESCRIPTION

[0029] The present application is further described in detail below in conjunction with embodiments and comparative examples.

[0030] Example 1 An alloy powder suitable for surface treatment of a petroleum screw, comprising a first powder raw material, a second powder raw material and a functional auxiliary mixture raw material, wherein the composition of the first powder raw material and its corresponding weight are shown in Table 1, the composition of the second powder raw material and its corresponding weight are shown in Table 2, and the composition of the functional auxiliary mixture raw material and its corresponding weight are shown in Table 3; The weight ratio of the first powder raw material, the second powder raw material and the functional auxiliary mixture raw material is 1:1:0.3; the particle size of the alloy powder suitable for surface treatment of petroleum screw is 15.5 μm.

[0031] Embodiment 2-4 An alloy powder suitable for surface treatment of a petroleum screw rod, which is different from Example 1 in that the composition of the first powder raw material and its corresponding weight are shown in Table 1.

[0032] Table 1 Composition and weight portions of the first powder raw material in Examples 1-4 (kg / portion) raw material Example 1 Example 2 Example 3 Example 4 Tungsten 70 70 65 75 cobalt 22 22.5 20 25 carbon 4 6 4 8 Alumina 4 4 3 5 Embodiment 5-7 An alloy powder suitable for surface treatment of a petroleum screw, which is different from Example 1 in that the composition of the second powder raw material and its corresponding weight are shown in Table 2.

[0033] Table 2 Composition and weight portions of the second powder raw material in Examples 1, 5-7 (kg / portion) raw material Example 1 Example 5 Example 6 Example 7 chromium 10 10.5 9 12 boron 6 6.5 5 8 silicon 5 5 4 6 nickel 65 65 50 80 Examples 8-10 An alloy powder suitable for surface treatment of petroleum screws, which is different from Example 1 in that the components of the functional auxiliary mixture raw materials and their corresponding weights are shown in Table 3.

[0034] Table 3 Compositions and weight portions of the raw materials of the functional auxiliary mixture in Examples 1, 8-10 (kg / portion)

[0035] Embodiment 11 An alloy powder suitable for surface treatment of petroleum screws, which is different from Example 1 in that the weight ratio of the first powder raw material, the second powder raw material and the functional auxiliary mixture raw material is 0.8:1:0.2.

[0036] Example 12 An alloy powder suitable for surface treatment of petroleum screws, which is different from Example 1 in that the weight ratio of the first powder raw material, the second powder raw material and the functional auxiliary mixture raw material is 1.2:1:0.4.

[0037] Embodiment 13 An alloy powder suitable for surface treatment of a petroleum screw rod, which is different from Example 1 in that the particle size of the alloy powder suitable for surface treatment of a petroleum screw rod is 13 μm.

[0038] Embodiment 14 An alloy powder suitable for surface treatment of a petroleum screw rod, which is different from Example 1 in that the particle size of the alloy powder suitable for surface treatment of a petroleum screw rod is 18 μm.

[0039] Embodiment 15 An application method of alloy powder suitable for surface treatment of petroleum screws comprises the following steps: (1) Preparing a first powder raw material, a second powder raw material and a functional auxiliary mixture raw material; (2) After the first powder raw material, the second powder raw material and the functional auxiliary mixture raw material are mixed, the surface of the screw rotor is thermally sprayed, and a cladding layer is obtained by laser cladding to complete the surface treatment of the screw rotor.

[0040] Note: In the above operation, the thickness of the cladding layer is 40 μm; the temperature of thermal spraying is 1200 °C; the laser wavelength of laser cladding is 10 μm, the laser scanning speed is 0.9 m / min, and the laser power density is 15 kW / cm 2 .

[0041] Example 16 A method for applying alloy powder suitable for surface treatment of petroleum screws, which is different from Example 15 in that the thickness of the cladding layer in step (2) is 20 μm.

[0042] Embodiment 17 A method for applying alloy powder suitable for surface treatment of petroleum screws, which is different from Example 15 in that the thickness of the cladding layer in step (2) is 30 μm.

[0043] Embodiment 18 A method for applying alloy powder suitable for surface treatment of petroleum screws, which differs from Example 15 in that in step (2), the temperature of thermal spraying is 1000°C.

[0044] Embodiment 19 A method for applying alloy powder suitable for surface treatment of petroleum screws, which differs from Example 15 in that in step (2), the temperature of thermal spraying is 1400°C.

[0045] Embodiment 20 An application method of alloy powder suitable for surface treatment of petroleum screws, which is different from Example 15 in that in step (2), the laser wavelength of laser cladding is 10 μm, the laser scanning speed is 0.6 m / min, and the laser power density is 10 kW / cm 2 .

[0046] Embodiment 21 An application method of alloy powder suitable for surface treatment of petroleum screws, which is different from Example 15 in that in step (2), the laser wavelength of laser cladding is 12 μm, the laser scanning speed is 1.2 m / min, and the laser power density is 20 kW / cm 2 .

[0047] Comparative Example 1 An alloy powder suitable for surface treatment of petroleum screws, which is different from Example 1 in that no functional auxiliary admixture raw material is used.

[0048] Comparative Example 2 An alloy powder suitable for surface treatment of petroleum screws, which is different from Example 1 in that molybdenum is not used in the components of the functional auxiliary mixture raw material.

[0049] Comparative Example 3 An alloy powder suitable for surface treatment of petroleum screws, which is different from Example 1 in that titanium is not used in the components of the functional auxiliary mixture raw material.

[0050] Comparative Example 4 An alloy powder suitable for surface treatment of petroleum screws, which is different from Example 1 in that niobium is not used in the components of the functional auxiliary admixture raw material.

[0051] Comparative Example 5 An alloy powder suitable for surface treatment of petroleum screws, which is different from Example 1 in that molybdenum and titanium are not used in the components of the functional auxiliary mixture raw material.

[0052] Comparative Example 6 An alloy powder suitable for surface treatment of petroleum screws, which is different from Example 1 in that molybdenum and niobium are not used in the components of the functional auxiliary mixture raw material.

[0053] Comparative Example 7 An alloy powder suitable for surface treatment of petroleum screws, which is different from Example 1 in that titanium and niobium are not used in the components of the functional auxiliary mixture raw material.

[0054] Performance testing Test samples: A commercially available NETZSCH screw stator rotor NM031BY01P05B was selected, and the rotor material was cast iron. The alloy powder suitable for surface treatment of petroleum screws in Examples 1-14 and Comparative Examples 1-7 was used to surface treat the rotor, and the surface treatment method was obtained in Example 15, and test samples 1-14 and control samples 1-7 were obtained. At the same time, the alloy powder suitable for surface treatment of petroleum screws in Example 1 was used to surface treat the rotor using the methods in Examples 16-21, respectively, and test samples 15-20 were obtained.

[0055] Test method: (1) High temperature resistance test: the screw pump rotor is placed in a high temperature environment for testing using a Bona 1400°C muffle furnace. The test temperature should reach or exceed the designed high temperature tolerance limit. The limit temperature of the screw pump rotor is determined by observing the deformation, cracks or other damage of the rotor. (2) Corrosion resistance test: place the screw pump rotor sample in a salt spray test chamber to simulate the salt spray conditions in an industrial atmosphere. The test conditions are 35°C ± 2°C and the salinity is 5% ± 1% until corrosion is observed on the rotor. The test duration is recorded. (3) Wear resistance test: test the screw pump rotor according to the content of GB / T 12444-2006 "Metallic material wear test method test ring-test block sliding wear test" and record the wear amount; The above-mentioned high temperature resistance test, corrosion resistance test and wear resistance test are carried out on the unsurface-treated screw rotor, and the initial values ​​obtained are recorded as A, B and C respectively; then the above-mentioned test is carried out on the surface-treated screw rotor in the same way, and the values ​​obtained are recorded as a, b and c respectively; finally, the high temperature resistance improvement rate, corrosion resistance improvement rate and wear resistance reduction rate are calculated, wherein the high temperature resistance improvement rate = (aA) / A, the corrosion resistance improvement rate = (b - B) / B, and the wear resistance reduction rate = (C - c) / C; After completing the above tests on test samples 1-20 and control samples 1-7 in sequence, the corresponding results are recorded in Table 4.

[0056] Table 4 Test results of test samples 1-20 and control samples 1-7 sample High temperature resistance improvement rate (%) Corrosion resistance improvement rate (%) Wear resistance reduction rate (%) Test sample 1 37.7 16.3 23.9 Test sample 2 36.2 14.8 22.4 Test sample 3 36.8 15.4 23.0 Test sample 4 36.5 15.1 22.7 Test sample 5 37.1 15.7 23.3 Test sample 6 36.4 15.0 22.6 Test sample 7 37.5 16.1 23.7 Test sample 8 37.2 15.8 23.4 Test sample 9 36.6 15.2 22.8 Test sample 10 38.1 16.7 24.3 Test sample 11 36.9 15.5 23.1 Test sample 12 36.7 15.3 22.9 Test sample 13 37.0 15.6 23.2 Test sample 14 36.3 14.9 22.8 Test sample 15 36.0 14.6 22.2 Test sample 16 37.3 15.9 23.5 Test sample 17 37.5 16.1 23.7 Test sample 18 37.4 16.0 23.6 Test sample 19 36.5 15.1 22.7 Test sample 20 36.9 15.5 23.1 Control sample 1 7.6 2.1 4.2 Control sample 2 19.8 7.0 11.4 Control sample 3 18.1 6.1 10.6 Control sample 4 20.5 7.6 12.2 Control sample 5 12.8 3.8 7.0 Control sample 6 14.9 5.3 8.6 Control sample 7 13.2 4.4 7.8 It can be seen from the combination of Examples 1-10 and Comparative Examples 1-7 and Table 4 that by using a functional auxiliary admixture raw material containing molybdenum, titanium and niobium, the first powder raw material and the second powder raw material can be used to play a relatively excellent role in improving the high temperature resistance, corrosion resistance and wear resistance; if only one or two of molybdenum, titanium and niobium are used in the functional auxiliary admixture raw material, the effect of improving the high temperature resistance, corrosion resistance and wear resistance is limited, and the corresponding effects are only simply superimposed on each other, and only when the three are used in combination can a significant improvement effect of 1+1>2 be brought. At the same time, it can be seen from the combination of Examples 11-12 and Table 4 that when the weight ratio of the first powder raw material, the second powder raw material and the functional auxiliary admixture raw material is (0.8-1.2):1:(0.2-0.4), a relatively excellent and stable application effect can be exerted, and when the weight ratio of the first powder raw material, the second powder raw material and the functional auxiliary admixture raw material is 1:1:0.3, the alloy powder suitable for surface treatment of petroleum screws shows a better application effect.

[0057] Combining Example 1 and Examples 13-14 with Table 4, it can be seen that when the particle size of the alloy powder suitable for the surface treatment of petroleum screws is 13-18 μm, the effect of cooperation between them is better, and can show excellent and stable high temperature resistance, corrosion resistance and wear resistance improvement effects.

[0058] Combining Example 1 and Examples 16-17 with Table 4, it can be seen that the thickness of the cladding layer in step (2) is 20-40 μm, which can meet the requirements of screw rotor surface treatment and show excellent and stable high temperature resistance, corrosion resistance and wear resistance improvement effects.

[0059] Combining Example 1 and Examples 18-21 with Table 4, it can be seen that when the alloy powder suitable for surface treatment of petroleum screws is used, the temperature of thermal spraying is 1000-1400°C, the laser wavelength of laser cladding is 10-12μm, the laser scanning speed is 0.6m / min-1.2m / min, and the laser power density is 10-20kW / cm 2 , all of which can fully coordinate and combine the first powder raw material, the second powder raw material and the functional auxiliary mixture raw material. The high temperature resistance improvement rate, corrosion resistance improvement rate and wear resistance reduction rate obtained by testing are all relatively excellent.

[0060] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. An alloy powder suitable for surface treatment of petroleum screws, characterized in that: It includes a first powder raw material, a second powder raw material and a functional auxiliary mixture raw material; The first powder raw material comprises the following components in parts by weight: Tungsten 65-75 parts; Cobalt 20-25 parts; Carbon 4-8 parts; 3-5 parts of aluminum oxide; The second powder raw material comprises the following components in parts by weight: Chromium 9-12 parts; Boron 5-8 parts; Silicon 4-6 parts; Nickel 50-80 parts; The functional auxiliary mixture raw material comprises the following components in parts by weight: Molybdenum 8-10 parts; Titanium 80-90 parts; Niobium 3-5 parts; The weight ratio of the first powder raw material, the second powder raw material and the functional auxiliary mixture raw material is (0.8-1.2):1:(0.2-0.4).

2. The alloy powder suitable for surface treatment of petroleum screw according to claim 1, characterized in that: The weight ratio of the first powder raw material, the second powder raw material and the functional auxiliary mixture raw material is 1:1:0.

3.

3. The alloy powder suitable for surface treatment of petroleum screw according to claim 1, characterized in that: The first powder raw material comprises the following components in parts by weight: Tungsten 70 parts; Cobalt 22 parts; 4 parts of carbon; 4 parts of aluminum oxide.

4. The alloy powder suitable for surface treatment of petroleum screw according to claim 1, characterized in that: The second powder raw material comprises the following components in parts by weight: Chromium 10 parts; Boron 6 parts; Silicon 5 parts; Nickel 65 parts.

5. The alloy powder suitable for surface treatment of petroleum screw according to claim 1, characterized in that: The functional auxiliary mixture raw material comprises the following components in parts by weight: Molybdenum 10 parts; Titanium 85 parts; Niobium 5 parts.

6. The alloy powder suitable for surface treatment of petroleum screw according to claim 1, characterized in that: The particle size of the alloy powder suitable for surface treatment of petroleum screws is 13-18 μm.

7. The application method of the alloy powder suitable for surface treatment of petroleum screws according to claim 1, characterized in that: The following steps are involved: (1) Preparing a first powder raw material, a second powder raw material and a functional auxiliary mixture raw material; (2) After the first powder raw material, the second powder raw material and the functional auxiliary mixture raw material are mixed, the surface of the screw rotor is thermally sprayed, and a cladding layer is obtained by laser cladding to complete the surface treatment of the screw rotor.

8. The method for applying the alloy powder suitable for surface treatment of petroleum screw according to claim 7, characterized in that: The thickness of the cladding layer in step (2) is 20-40 μm.

9. The method for applying the alloy powder suitable for surface treatment of petroleum screw according to claim 7, characterized in that: In step (2), the temperature of thermal spraying is 1000-1400°C.

10. The application method of the alloy powder suitable for surface treatment of petroleum screw according to claim 7, characterized in that: In step (2), the laser wavelength of laser cladding is 10-12 μm, the laser scanning speed is 0.6 m / min-1.2 m / min, and the laser power density is 10-20 kW / cm 2 .

Citation Information

Patent Citations

  • Spherical tungsten carbide and nickel-based alloy mixed powder for screw strengthening and laser cladding method

    CN115383110A

  • Oxide particle reinforced laser cladding high-wear resistance nickel-base alloy powder and preparation method thereof

    CN103014475A

  • Wear-resistant and corrosion-resistant composite coating on surface of screw rod of injection molding machine and preparation method thereof

    CN117701947A

  • Carbon-oxygen corrosion resistant coating powder material and preparation method of carbon-oxygen corrosion resistant coating

    CN119464845A

  • Corrosion resistant self-fluxing alloys for thermal spraying

    EP0223135A1